In vitro culture techniques as a tool of sugarcane bud germination study under salt stress - GANDONOU, GBOSSÈGNON CHRISTOPHE BERNARD; AGBANGLA, CLÉMENT; AHANHANZO, CORNEILLE; ERRABII, Tomader; IDAOMAR, Mohamed; ABRINI, Jamal; SKALI SENHAJI, Nadia (My University, 2008)
Germination was the first stage confronted to soil salinity and it is important to determine salt effects on this stage. In this study, we reported an in vitro procedure for studying sugarcane bud germination and shoot growth under salt stress with different NaCl concentrations (0, 17, 34, 68 and 102 mM) using cultivar NCo310. Germination percentage of control was about 92% after 8 days. Germination of buds, plant fresh and dry mass decreased with increasing salinity. Data indicated that in vitro culture techniques could be used to evaluate salt stress effects in sugarcane at the germination stage.
Keywords: in vitro culture; sugarcane; buds germination; salt stress; shoot growth